Building Africa’s climate resilience: understanding the impacts and future strategies in the face of climate change - Ayompe, Lacour M.; Epie, Wesner N. (Frontiers in Climate, 2025)
Climate change is reshaping Africa’s environmental, economic, and social landscapes, intensifying vulnerabilities across agriculture, water resources, public health, and socioeconomic stability. This paper examines the multifaceted impacts of a changing climate on key sectors in Africa and highlights the urgent need for integrated adaptation strategies. Through the synthesis of traditional wisdom and modern innovations, the study showcases how indigenous knowledge, community-led initiatives, and climate-smart agricultural practices contribute to enhanced resilience. Case studies from diverse regions demonstrate the effectiveness of combining traditional practices with advanced technologies, while policy and governance frameworks emphasize the importance of inclusive, data-driven decision-making. The research further addresses critical investment gaps and advocates for robust financial and technical support to empower local communities in managing climate risks. By leveraging established frameworks such as the African Climate Resilience Acceleration roadmap and fostering cross-sectoral collaboration, the paper outlines forward-looking strategies that could mitigate immediate climate threats and lay the groundwork for sustainable development. Ultimately, through coordinated efforts and strategic investments, African nations can transform the challenges of climate change into opportunities for resilience and growth.